Temperature dependency of linear viscoelastic properties of a commercial low-fat soft cheese after frozen storage - Meza, Barbara Erica del Valle (2012)
The temperature dependency of linear viscoelastic properties of a commercial low-fat soft cheese containing microparticulated whey protein as fat replacer was studied considering the effect of freezing. After thawing, cheeses were held at 6 C during 48 days for ripening. Refrigerated cheeses (stored at 6 C for 48 days) were used as control samples. Frequency sweeps (0.01-10 Hz) in the linear viscoelastic region at 10, 20, 30, 40, and 50 C were performed. Activation energies for complex viscosity at 1 Hz were obtained from an Arrhenius-type equation. Also, the time-temperature superposition method, the modified Cole-Cole analysis and the weak gel model for foods were used to compare the behavior of frozen and refrigerated cheeses. The results obtained in this work indicated that the viscoelastic properties of the studied cheeses obtained at different temperatures were influenced by freezing.